Upaya Peningkatan hasil Belajar Passing dalam Sepakbola Menggunakan Pendekatan Drill dan Permainan di Kelas V-B SDN Putat Gede 1/94 Surabaya - Adam Fahry Surya Pratama; Bambang Feriyanto Tjahyo Kuntjoro; Yohanes Giovani Pion Makung (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The outcomes of teaching football passing skills to pupils in the VB class at SDN Putat Gede 1/94 Surabaya. Initially, there were numerous scores that fell below the criterion. This is substantiated by a mere 60% of the overall student population. Considering this objective, the researcher intends to carry out Classroom Action Research (PTK) utilising drill and game techniques to enhance student learning results in the VB class at SDN Putat Gede 1/94 Surabaya. After employing a methodology that combines drilling exercises and interactive games. The method is executed in two cycles, each consisting of two games. During cycle 1, there was a rise from 60% to 68%. Furthermore, during cycle II, there was a notable rise from 68% to 80%, which mirrors the increase observed in cycle I. Based on these findings, it can be inferred that utilising drill and game techniques can enhance the educational achievements in passing content for VB class students at SDN Putat Gede 1/94 Surabaya.